Knowledge in the Performance of Newborn Hearing Screening Test of Nurses in Private Hospitals - Liezel Lorraine B. Olivo; Xerxes G. Malaga (Philippine Social Science Journal, 2020)
The newborn hearing screening test is implemented before hospital discharge to initiate early identification and treatment. With a large population, lack of education, fewer professionals, and limited access to facilities, the targeted hearing screening program is implemented only to high-risk infants. The success in mandating Republic Act No. 9709, also known as the Universal Newborn Hearing Screening and Intervention Act of 2009, was enacted for the prevention, early diagnosis, and intervention of hearing loss. Healthcare professionals do not feel adequately updated with newborn hearing screening and documenting screening results. Hence, this paper describes the level of knowledge of nurses in performing newborn hearing screening tests. Likewise, it determines the difference existing between nurses' demographics and their level of knowledge. Also, it identifies nurses' level of knowledge based on areas of procedures, standards, and protocols of newborn hearing screening tests and challenges and best practices encountered.